Installation of Citizenship Culture Through Elementary School Students Learning Music Arts - Sahputra, Dimas; Ivana, Julia (Berpusi Publishing, 2023)
The purpose of the study is to explain how the art of music is used to create an optimal culture of citizenship to carry out innovation and creativity in conveying learning material. In addition, teachers must also be able to integrate interesting learning models but also apply conventional methods so that the material conveyed contains elements of civic culture. Technically, this learning is quite easy, namely the teacher chooses songs that are familiar to students and easy to memorize. This method is expected to be able to create effective and efficient learning so that students are able to form a culture of citizenship in students as the nation's generation